Is ambulance conveyance associated with distance to hospital and patient outcomes? A register-based cohort study in Region Zealand, Denmark, 2017–2022 - Stig Nikolaj Fasmer Blomberg; Signe Amalie Wolthers; Annette Ersbøll; Helle Collatz Christensen; Josefine Tangen Jensen; Thea Palsgaard Møller (BMJ Open)
Background Non-conveyance, the decision not to transport a patient to a healthcare facility, can result from patient refusal or the ambulance professional’s decision. Distance to hospital may influence decisions on non-conveyance, which offers benefits such as reduced pressure on emergency departments, quicker ambulance availability and potentially better patient comfort.Objectives The aim of this study was threefold: (1) to determine the proportion of patients attended by an ambulance and not subsequently transported to a hospital (non-conveyance), (2) to study whether distance to hospital is associated with non-conveyance, and (3) to examine the association between non-conveyance and subsequent contact to the healthcare system and mortality within both 48 hours and 30 days from the primary contact.Design, setting and participants A register-based cohort study of emergency ambulance dispatches (priority A or B) from October 2017 to December 2022 in Region Zealand, Denmark. Data were linked to national registries using patients’ personal identification numbers.Outcome measures and analysis The proportion of non-conveyed patients was calculated. The association between distance to allocated hospital and non-conveyance and the association between non-conveyance and subsequent contact with the healthcare system and mortality were analysed using logistic regression analyses.Results A total of 383 611 ambulance dispatches were included. Overall, 16.6% (95% CI: 16.4; 16.6) of the patients were non-conveyed during the study period. The annual proportion increased from 12.3% (95% CI: 11.7; 12.9) in 2017 to 19.8% (95% CI: 19.6; 20.1) in 2022. A longer distance to the allocated hospital was associated with higher odds for non-conveyance. Odds for non-conveyance were 1.82 (95% CI: 1.76; 1.88) times higher for distances 40–50 km compared with distances 0–10 km. A higher odds of subsequently contacting the healthcare system was found for non-conveyed patients, while there were lower odds for mortality.Conclusion The proportion of non-conveyed patients increased from 2017 to 2022. Non-conveyance increased with an increasing distance to the allocated hospital (p for trend <0.001). Mortality was lower for non-conveyed patients, but further research is needed to conclude on the safety of this practice.Registration The regional Research Register in Region Zealand approved the study, REG-145-2023.